Ethnoecology: The Mythology of the Cili Buyut of the Osing Kemiren Society, Banyuwangi - Jamil, Robit Nurul; Na’im, Mohammad; Swastika, Kayan; Sumarjono, Sumarjono; Pratama, Akhmad Ryan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Banyuwangi, which is popular for its beautiful natural landscapes, also has a diverse culture ranging from arts to various traditional ceremonies. This cultural diversity continues to be collectively preserved by the community. Banyuwangi residents are quite diverse. One of the wisdoms found in relation to environmental protection is the indigenous people of Kemiren village. About his trust in Great-grandfather Chili's site. The Osing people in Kemiren village have many traditions originating from their ancestral culture. Ownership includes arts, traditional rituals, languages, etc. All public and private activities always refer to the existence of the great-grandfather site of Chile, which is manifested in the form of a nguri or slametan at his tomb. In this sense, the grave sites of Chile's great-grandfathers are not a ban, but a restriction on the use of the natural environment. Local wisdom was born from the grave site of Chile's great-grandfather. Then a public trust that can protect the environment. Several important aspects of the environment can be maintained until now, such as water sources, soil fertility, fields, rice fields, and ecosystem balance.